Penetration of fleroxacin into breast milk and pharmacokinetics in lactating women. - Dan, M (1993)
Fleroxacin was administered to seven lactating women as a single oral dose of 400 mg. Plasma, urine, and milk samples were collected for up to 48 h after administration. Drug concentrations were determined by a reversed-phase high-pressure liquid chromatography method and were used for the pharmacokinetic evaluation. At approximately 2 h after oral administration, a maximum concentration of 5.6 mg/liter was determined in plasma; the area under the plasma concentration-time curve (AUC) amounted to 70.3 mg.h/liter, and the elimination half-life in the postdistributive phase was 8 h. Total systemic clearance was 97.3 ml/min, and urinary excretion was 38% of the dose within 48 h. In addition, 8.6% of the N-demethyl metabolite and 4.4% of the N-oxide metabolite were recovered from urine. In comparison with previous results obtained with healthy male volunteers, the time to reach maximum concentrations in plasma was twice as long in the nursing women, and total clearance as well as urinary elimination were reduced by 25%. In breast milk, the mean maximum concentration was 3.5 mg/liter, which was reached 2.6 h after drug administration. The elimination half-life of fleroxacin in milk was identical to that in plasma, and the AUC reached 43.3 mg.h/liter. On the basis of the comparison of the AUC in milk versus the AUC in plasma, the proportion of fleroxacin penetration into milk was 62%. The cumulative excretion in milk amounted to only 0.219 mg within 48 h. On the basis of an average daily intake of milk of a breast-fed child of 150 ml/kg of body weight, the maximum daily ingested fleroxacin dose would not exceed 10 mg. However, quinolones are known to induce arthropathy in juvenile animals, and therefore, administration of fleroxacin to breast-feeding women cannot be allowed.